Comparing ARF and Six Party Talks in the North Korean Nuclear Issue: A Regional Institution Approach - Pratama, Eros (Andalas Institute of International Studies, 2023)
The North Korean Nuclear Issue is one of the post-World War II problems that are not yet settled after the Cold War concluded. This issue has been escalated at least to the regional level that is being discussed not only by the two Koreas but also by some regional parties particularly in Asia. Two of the most well highlighted regional fora that handle the issue are the Six Party Talks and the ASEAN Regional Forum (ARF). The existence of the two fora itself able to represent the two camps of regional studies in describing the dialogues on North Korean Nuclear issue: Global power-led and the multilateral mechanism-led. This paper is basically comparing the manifestations of these two camps. The result showed that for the case of North Korea issue, the multilateralist ARF able to consistently deal with the issue longer even though the progress is relatively low. The Six Party Talks is in contrast where with more ambitious goal, more dedicated forum to the issue, and larger involvement of the global powers, the Talks was unable to maintain its existence for a longer time nor achieve the expected progress.